Optimal cutoffs of growth discordance for the risk of preeclampsia in twin pregnancies: A single-center retrospective cohort study - Zhu, Jie; An, Ping; Zhao, Huanqiang; Zhao, Ying; Zhou, Jizi; Zhou, Qiongjie; Li, Xiaotian; Xiong, Yu (Frontiers in Cardiovascular Medicine, 2023)
Objective To explore the optimal cutoffs of growth discordance for the risk of preeclampsia in twin pregnancies. Methods A retrospective cohort study in a university hospital which included twins delivered from February 2013 to September 2020. Restrictive cubic spline (RCS) model was applied to the trend of intertwin birthweight difference (BWD) with the risk of preeclampsia. Logistic regression and subgroup analysis were performed to find the cut-off with statistical significance and clinical meaningfulness. Results A total of 2,631 women pregnant with twins were enrolled. RCS showed a nonlinear upward trend of preeclampsia with BWD, and the BWD of 15% was the initial rising point. With the confounders adjusted, only the group with BWD ≥ 25% was found to be significantly associated with an increased risk of preeclampsia (adjusted odds ratio [aOR], 2.44; 95% confidence interval [CI]: 1.74–3.42). Additionally, subgroup analysis showed that both monochorionic (MC) and small for gestational age (SGA) twins were more likely to complicate with preeclampsia. Conclusion The growth discordance of 15% during pregnancy may be the preventive point of preeclampsia, and 25% may be the interventional point.